459PFish intake, dietary polyunsaturated fatty acids, and lung cancer: systematic review and dose-response meta-analysis of 1.7 million men and women. (24th November 2019) - Cao, C; Li, Y; Jiang, Q
Abstract: Background: Lung cancer is the most frequently diagnosed cancer and the leading cause of cancer death among males and females. There is evidence that diet habit may influence lung cancer risk. To determine the association between fish intake and dietary polyunsaturated fatty acids (PUFA) and incidence of lung cancer, we identified all available studies to clarify the dose-response relationship between fish and PUFA and lung cancer risk, evaluated the potential effects of frequent fish and PUFA intake on lung cancer mortality, and studied the ability of their supplementations during chemotherapy in patients with lung cancer. Methods: We systematically reviewed and meta-analyzed the published studies in MEDLINE, EMBASE databases, Cochrane Library database (Cochrane central register of controlled trials) and ClinicalTrials, supplemented with manual screening. Large-scale prospective cohort study and randomized control trials quantifying the associations of fish and PUFA consumption with risk of lung cancer were included. Two investigators dependently assessed studies for inclusion and extracted data on methods, interventions, outcomes and study quality. Relative risk (RR) with 95% confidence interval (CI) was calculated. Results: 13 population-based prospective cohort studies involving 1, 785, 000 participants and 2 randomized control trials were included. Our study demonstrated that dietary PUFA significant reduced risk of lung cancer for men (RR 0.99, 95%CI 0.98 to 1.00) and USA population (RR 0.99, 95%CI 0.98 to 1.00). Dose-response analysis indicated that a 5g/day increment of dietary PUFA was associated with 5% lower risk of lung cancer (RR 0.95, 95%CI 0.91 to 0.99). In addition, PUFA supplementation is significant improved overall survival in patients with lung cancer (RR 1.98, 95%CI 1.09 to 3.59). Conclusions: Our study showed an inverse association between dietary PUFA and risk of lung cancer in males and among USA population. Although smoking cessation is the single biggest factor associated with lung cancer risk reduction, this study adds to a growing body of evidence that diet may have a role in modestly reducing lung cancer risk. Editorial acknowledgement: This work was supported by program for the National Natural Science Foundation of China (grant number 81700025), the Medical and Health Science and Technology Project of Zhejiang (grant number 2018245859), the Medical Science and Technology Plan Projects of Ningbo (grant number 2016A03), the Science Foundation of Zhejiang (grant number LY15H010002) and the Beijing Medical Health Foundation (grant number YWJKJJHKYJJ-HX32). Legal entity responsible for the study: The authors. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.